A pilot study to examine the acceptability and health effects of electronic cigarettes in HIV-positive smokers. (1st January 2020) - Cioe, Patricia A.; Mercurio, Alana N.; Lechner, William; Costantino, Catherine C.; Tidey, Jennifer W.; Eissenberg, Thomas; Kahler, Christopher W.
Highlights: Smoking cessation rates are substantially lower among persons living with HIV (PLWH). Electronic cigarettes may be a viable option for smokers who are unable or unwilling to quit smoking combustible cigarettes. At week 8, cigarettes per day (CPD) were reduced by more than 80%, with reduction maintained at week 12. ECs may be promising as a harm reduction approach among HIV-positive smokers who are unable or unwilling to quit smoking. Abstract: Introduction: Some HIV-positive smokers report ambivalence about quitting. Switching to electronic cigarettes (ECs) may be a viable option to reduce the negative health effects for smokers who are unable or unwilling to quit smoking combustible cigarettes (CCs). This study examined the acceptability and health-related effects of ECs in HIV-positive smokers who were not seeking smoking cessation treatment. Methods: HIV-positive smokers (N = 19) were enrolled and followed for 12 weeks. Cartridge-based ECs were provided at baseline, and E-liquid was provided weekly for 8 weeks. At baseline, weeks 1–8, and week 12, EC and CC use, cardiopulmonary function, respiratory symptoms, and carbon monoxide (CO) levels were measured. Results: At week 8, cigarettes per day (CPD) were reduced by more than 80%, with reduction maintained at week 12 ( p' s < .001). Cigarette dependence scores were 40% lower at week 8 than at baseline ( p < .001). Seven (36.8%) participants reported transitioning completely from CCs to ECs. Mean CO decreased significantly from BL to week 8 ( p < .05) and remained significantly lower at week 12 ( p < .001). Intention to quit increased significantly over time. Conclusions: Switching from CCs to ECs in HIV-positive smokers who are not ready to quit smoking in the next 30 days appears to be feasible. Beneficial effects were seen, such as reduced CPD, reduced CO and CC dependence, and increased motivation to quit. ECs may be promising as a harm reduction approach among HIV-positive smokers who are unable or unwilling to quit smoking.